Tidi Da'a Learning Through Demonstration Method in Extracurricular Activities in SMA Negeri 1 Telaga - Moh ikbal lapanco; Nurlia Djafar; Trubus Semiaji; Riana Diah Sitharesmi; Mimy Astuty Pulukadang (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research is motivated by the dominant development of creative dance in dance extracurricular activities at SMA Negeri 1 Telaga. This is evident from the various achievements achieved by students in dance competitions at the district and provincial levels, most of which are oriented towards creative dance. Creative dance is considered more interesting, varied, and in line with current developments, so it is more popular with students than traditional dance. This condition causes traditional dance learning, especially Tidi Da'a, to become less dominant in extracurricular activities. Nevertheless, the school continues to strive to preserve regional culture through traditional dance learning by implementing demonstration methods in the Tidi Da'a learning process. This study aims to describe the Tidi Da'a learning process through demonstration methods in extracurricular activities at SMA Negeri 1 Telaga. The research method used is a descriptive qualitative method. Data collection techniques are carried out through observation, interviews, and documentation. The research subjects consist of dance extracurricular instructors and students who participate in dance extracurricular activities. The results of the study indicate that the Tidi Da'a learning process through the demonstration method is carried out through several stages, namely an introduction to the history and meaning of the dance, a demonstration of movements by the instructor, repeated movement exercises, and evaluation based on the wiraga, wirama, and wirasa aspects. The demonstration method is considered effective because it makes it easier for students to understand and imitate the dance movements directly. In addition, learning Tidi Da'a in extracurricular activities is one of the school's efforts to preserve regional culture amidst the dominant interest of students in creative dance and the influence of digital culture.